016 PP: INSIDERS AND OUTSIDERS: THE EXPERIENCE OF CO-RESEARCHERS EXPLORING AUTISM IN A SOMALI COMMUNITYa. (3rd March 2017) - Fox, F; Aabe, N; Turner, K; Rai, D; Redwood, S
Abstract : Rates of autism in Somali migrant communities are increasing but many families find it hard to accept their child's diagnosis and do not engage with health, education or social services to support their children. When a local network of Somali parents approached the University of Bristol to request that research focus on their needs, a new research partnership evolved. Using a community based participatory approach the team designed a qualitative study which aimed to assess what Somali families affected by autism need, and how health, education and social care services can support them. In-depth interviews were conducted in both English and Somali with 15 parents who had a child with autism. Key themes identified in the data increased understanding about the experiences of Somali families affected by autism, cultural perceptions of autism and the challenges of navigating the health, education and social care system. In this presentation the co-researchers reflect upon their experiences of conducting research with this under represented group. They reflect on how they negotiated their status as insiders and outsiders, both within the Somali and research communities. The process of recruiting participants, conducting interviews together in two languages, jointly analysing the data and disseminating the findings is discussed, with particular focus on role boundaries and the successes and challenges encountered during the project. The presentation highlights the value of partnership working with local community groups to effectively conduct research and raise awareness about stigmatising conditions. a The research is supported by the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care West (CLAHRC West) at University Hospitals Bristol NHS Foundation Trust. The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health.